The substitute teaching survival guide emergency lesson plans and essential advice, grades K-5 - Dellinger, John (Jossey-Bass, 2006)
While most books for substitute teachers offer suggestions for classroom management, this volume provides an even more important resource: over 80 ready-to-use emergency lesson plans for language arts, mathematics, social studies, and science arranged by grade level. With 155 useful suggestions and a daily outline of activities, this guide offers substitute teachers in K-5 key information that will make the difference between a good day of teaching and a complete disaster.